Do Women Ask for Less? Evidence from Reservation Wages in Italy - Vincenzo Scoppa; Idola Francesca Spanò (Institute of Labor Economics (IZA), 2025)
Gender gaps in labor market outcomes have traditionally been attributed to differences in individual productivity or to discrimination. More recently, several studies have documented the role of gender differences in psychological attitudes. Rather than using data on realized wages, we rely on data on reservation wages – the lowest wage workers are willing to accept – for a sample of Italian graduates. Reservation wages reflect individual attitudes and beliefs more directly, while being less affected by employer discrimination. We first relate reservation wages to educational background, individual characteristics, and family background, and investigate how they depend on labor market expectations. We then analyze how reservation wages depend on preferences over specific job attributes, such as permanent positions, geographical mobility, etc. Applying the Gelbach decomposition to quantify the contribution of each factors, we find a substantial role for preferences for job attributes and expectations. However, our estimates reveal a large unexplained component which is likely driven by gender differences in psychological and social attitudes, such as risk aversion, overconfidence and adherence to social norms.
Keywords: J16; J32; D83; D91; 330; gender gaps; reservation wages; graduate labor market; psychological attitudes; behavioral economics